On pure phases of the Vannimenus model - Ganikhodjaev, Nasir; Uguz, Selman; Akin, Hasan; Temir, Seyit (American Institute of Physics, 2010)
One of the main problems of the Statistical Physics is to describe all Gibbs measures corresponding to the given Hamiltonian. It is well known that such measures form a nonempty convex compact subset in the set of all probabilistic measures. The purpose of this paper is to investigate Gibbs measures of the Vannimenus model.